2020
DOI: 10.1519/jsc.0000000000003086
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Eccentric, Concentric, and Eccentric-Concentric Isotonic Resistance Training at Two Velocities on Strength and Muscle Hypertrophy

Abstract: Ünlü, G, Çevikol, C, and Melekoğlu, T. Comparison of the effects of eccentric, concentric, and eccentric-concentric isotonic resistance training at two velocities on strength and muscle hypertrophy. J Strength Cond Res 34(2): 337–344, 2020—The aim of this study was to compare the effects of concentric, eccentric, and eccentric-concentric isotonic resistance training at both fast and slow velocities to determine whether contraction modality affects muscle strength and hypertrophy. Forty-one young, healthy males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
2
12
1
Order By: Relevance
“…Several studies have demonstrated the benefit of eccentric rehabilitation in terms of muscle strength gain compared with concentric reinforcement, while other authors found no difference between the two types of exercises. 20,[28][29][30] In our study, although we did not find any in M MAX , we identified an increase in muscle contraction at rapid velocity (M MAX 150°/s) in the eccentric group and an increase in P MAX muscle power. This can be explained by the fact that power is equal to the product of force and velocity.…”
Section: Discussioncontrasting
confidence: 80%
“…Several studies have demonstrated the benefit of eccentric rehabilitation in terms of muscle strength gain compared with concentric reinforcement, while other authors found no difference between the two types of exercises. 20,[28][29][30] In our study, although we did not find any in M MAX , we identified an increase in muscle contraction at rapid velocity (M MAX 150°/s) in the eccentric group and an increase in P MAX muscle power. This can be explained by the fact that power is equal to the product of force and velocity.…”
Section: Discussioncontrasting
confidence: 80%
“…Therefore, the combined isotonic contraction technique might be more successful than the repeated stretching technique in terms of increasing the knee extensor muscle strength. Previous studies have reported that when eccentric exercises are added to the concentric exercise program, a considerable increase in muscle strength is obtained [18]. At the same time, the current literature also suggests that the combined application of concentric, eccentric, and isometric exercises should be executed to maximize muscle strength [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that when eccentric exercises are added to the concentric exercise program, a considerable increase in muscle strength is obtained [18]. At the same time, the current literature also suggests that the combined application of concentric, eccentric, and isometric exercises should be executed to maximize muscle strength [17][18][19]. In some previous studies, improvement in muscle strength was achieved with the application of the PNF methods, which was depicted in our study as well [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In maximal efforts, eccentric force has repeatedly been reported significantly higher than concentric in the literature [ 16 , 17 ]. The difference in force between maximal eccentric and eccentric-concentric actions, however, is not well studied in strength-training research [ 18 ] and is lacking in studies on NHE. While it could be said that there is an evidence-based preventive effect of NHE training [ 9 ], several fundamental issues such as how to perform this exercise when it comes to dosing and whether eccentric-only or eccentric-concentric muscle actions should be used is still not clear.…”
Section: Introductionmentioning
confidence: 99%